2005
DOI: 10.1080/15622970510029876
|View full text |Cite
|
Sign up to set email alerts
|

Whether ionizing radiation is a risk factor for schizophrenia spectrum disorders?

Abstract: The neural diathesis-stressor hypothesis of schizophrenia, where neurobiological genetic predisposition to schizophrenia can be provoked by environmental stressors is considered as a model of the effects of exposure to ionizing radiation. Analysis of information from electronic databases (MEDLINE, PsycINFO, EMBASE, Current Contents, Elsevier BIOBASE) and hand-made search was carried out. There are comparable reports on increases in schizophrenia spectrum disorders following exposure to ionizing radiation as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 123 publications
0
20
0
Order By: Relevance
“…Previous studies suggested that radiation exposure might represent a risk for schizophrenia in humans [75,76]. In 10,834 individuals irradiated in childhood for tinea capitis (mean dose = 1.5 Gy), no association was found between radiation exposure and risk of schizophrenia, although for the subgroup irradiated at < 5 years of age a trend was found (hazard ratio = 1.18, 95% CI = 0.96–1.44, p = 0.1) [75].…”
Section: Reviewmentioning
confidence: 99%
“…Previous studies suggested that radiation exposure might represent a risk for schizophrenia in humans [75,76]. In 10,834 individuals irradiated in childhood for tinea capitis (mean dose = 1.5 Gy), no association was found between radiation exposure and risk of schizophrenia, although for the subgroup irradiated at < 5 years of age a trend was found (hazard ratio = 1.18, 95% CI = 0.96–1.44, p = 0.1) [75].…”
Section: Reviewmentioning
confidence: 99%
“…Another effect that could also be attributed to exposure to ionizing radiation is schizophrenia spectrum disorders (Loganovsky & Loganovskaja, 2000;Loganovsky, Volovik, Manton, Bazyka, & Flor-Henry, 2005). There are three hypotheses concerning ionizing radiation as a risk factor for schizophrenia: 1) genetic (in off-spring of exposed); 2) prenatal exposure (neurodevelopmental hypothesis), and 3) diathesis-stressor hypothesis , while irradiation in adulthood is considered to be a new model of schizophrenia (Iwata, Suzuki, Wakuda, Seki, Thanseem, Matsuzaki, et al, 2008).…”
Section: 44mentioning
confidence: 99%
“…Moreover, the incidence of the disorder seemed to be higher in rural areas of India that have high natural background radiation [69].…”
Section: Psychiatric Effects Of High Doses Of Irmentioning
confidence: 98%
“…There is evidence of an increased incidence of schizophrenia spectrum disorders following exposure to atomic bombing radiation, RT or environment with high natural IR level [69]. In fact, a significant enhanced prevalence of schizophrenia has been reported in the survivors in Nagasaki [70].…”
Section: Psychiatric Effects Of High Doses Of Irmentioning
confidence: 99%
See 1 more Smart Citation